Assessing student perspectives on ChatGPT in higher education: a quantitative analysis - Muhammad Amin; Bimaa Mustaqim; Wegig Pratama; Abdul Muin Sibuea (IAES International Journal of Artificial Intelligence (IJ-AI), 2026)
The rapid advancement of artificial intelligence (AI) has transformed higher education, with ChatGPT increasingly used as an academic support tool. This study examines university students’ perceptions of ChatGPT in Indonesian higher education through a quantitative survey involving 56 undergraduate, master’s, and doctoral students at Universitas Negeri Medan. The survey assessed perceived ease of use, quality of responses, learning support, and ethical concerns related to ChatGPT usage. The results indicate that most students perceive ChatGPT as easy to use and helpful for understanding academic materials and improving learning efficiency. However, concerns regarding academic integrity, overreliance, and potential reductions in problem-solving skills were also identified. Significant differences in perceptions emerged across academic levels, with undergraduate students expressing higher enthusiasm, while postgraduate and doctoral students demonstrated greater caution toward ethical and pedagogical implications. These findings highlight both the opportunities and challenges of integrating generative AI into higher education. This study provides the first quantitative empirical evidence on ChatGPT perceptions in Indonesian higher education and underscores the importance of embedding AI literacy, ethical guidelines, and critical thinking strategies into university curricula to ensure responsible and effective AI adoption.